Análisis Jurídico y Comparado de la figura jurídica tenencia respecto al desarrollo integral de la hija o hijo de familia. - Rodríguez Muñoz, France Geovanna (2023)
The Children and Adolescents Code has considered that tenure refers to care and coexistence that parents have with respect to children either jointly or separately, that is, the obligation of parents to live together, raise and care for and provide everything necessary for the integral development of the child or adolescent. Established that tenure refers to the coexistence of parents with respect to their children, in order to watch over and protect the minor, what happens when there is no parental responsibility? within Ecuador, there are 4,333,264 children, of which six percent of them, do not coexist with any of their parents, for different factors such as the crisis that Ecuador presented and still presents, their parents have had to migrate, domestic violence, lack of care by one or both parents, lack of interest in having an emotional relationship with their children and even the death of one or both parents. The Constitution of the Republic of Ecuador expressly recognizes the type of extended family, that is, all members of a nuclear family. If the child is in circumstances of vulnerability, it is essential that a relative is already an aunt, grandmother who has the will and has what is necessary to take care of the minor who does not have his or her parents. In revising our Code on Children and Adolescents, specifically in chapter III tenure, parents are considered to be the only ones deserving of this right, that is, only they can be the ones who claim the tenure of their children. When a minor does not have the protection of parents and yes of a relative, this same seeks to safeguard the child with him so that later he does not arrive at a children's hostel, which could be psychologically harmful to the child, being limited and only claimed by parents, we are violating what our Constitution must ensure for the integral development of the child and adolescent, just as we are not applying the principle of equality before the courts. Finally, implementing and expanding this legal figure, we will achieve several points for the benefit of children and adolescents who do not have their parents to protect them, firstly, it is achieved that the Judges in matters of Children and Adolescents and the Multicompetent Judges at the national level can override the Principle of the Best Interests of the Child and not remain stagnant due to lack of norms, as well as the Judges do not resort to other rules in this case to only appoint guardians which is not a guarantee for the minor who in orphanhood, lastly it will be ensured that minors are not taken to children’s hostel where they often end up having sequelae that affect their development.